Danto and His Critics - Rollins, Mark (Cambridge Blackwell, 1993)
Updated and revised, the Second Edition of Danto and His Critics presents a series of essays by leading Danto scholars who offer their critical assessment of the influential works and ideas of Arthur C. Danto, the Johnsonian Professor Emeritus in the Department of Philosophy at Columbia University and long-time art critic for The Nation.
Keywords: Danto, Arthur C. -- 1924-2013; 20th Century (1901-2000); Esthetics